Effect of problem solving method on the performance of mathematics students in public secondary schools in Rwanda: A case of Karongi district - Emmanuel BYIRINGIRO (International Journal of Science and Research Archive, 2024)
The aim of this paper was to investigate the effect of problem solving method on the performance of Mathematics students in public day Schools in Rwanda” A case of Karongi District’. Simple random sampling technique was further applied to obtain Mathematics teachers and students of senior 4,5 and 6, making 783 target students. The study used a sample of 230 respondents from the sampled schools. The collected data was analyzed using descriptive statistics, correlation, and regression analysis through the statistical package for social science (SPSS) version 21. The data collected were analyzed using descriptive statistics and multiple regression. The results of the findings indicated that the teaching of mathematics via the problem solving method was more correlated with the performance of students in Karongi District (r = 0.708; p= 0.000). Multiple linear regression analysis showed that problem solving method contributed to 70.2% of variation on the performance, hence plays a vital role in performance of Mathematics students in public secondary schools in Karongi District. Additionally, it was further inferred that problem solving method increases positive attitudes toward learning Mathematics subject. The study recommended that the mathematics teachers should practice constructing questions to include problems that are relatively neither easy nor difficult, so that every student can practice, which will foster students’ creative.